Method of producing hydrogen, photo catalyst, and method of producing photo catalyst

By applying high-pressure torsion treatment to oxide semiconductors, the method improves hydrogen production efficiency by increasing visible light absorbance and photocatalytic activity, addressing the low efficiency of existing oxide semiconductors in visible light.

JP2025008275APending Publication Date: 2025-01-20MITSUI CHEMICALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023110284
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing oxide semiconductors, such as titanium dioxide, exhibit low photocatalytic activity in the visible light range, limiting the efficiency of hydrogen production using natural light.

Method used

The method involves using a photocatalyst with an oxide semiconductor that has been subjected to a high-pressure torsion treatment (HPT) to enhance its absorbance in the visible light range, satisfying the condition of A600/A300 ≥ 0.1 in its absorption spectrum, and optionally using a sacrificial agent or promoter to improve hydrogen production efficiency.

Benefits of technology

The treated oxide semiconductors demonstrate increased hydrogen production efficiency by utilizing a wider wavelength range of light, enhancing photocatalytic activity without additional costs or waste generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008275000001_ABST
    Figure 2025008275000001_ABST
Patent Text Reader

Abstract

To provide a hydrogen production method that uses a photocatalyst and is excellent in hydrogen production efficiency, a photocatalyst excellent in hydrogen production efficiency, and a method of producing a photocatalyst excellent in hydrogen production efficiency.SOLUTION: The hydrogen production method includes decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor, with an absorbance A300 at 300 nm and an absorbance A600 at 600 nm of the oxide semiconductor in its absorbance spectrum obtained by ultraviolet-visible spectrometry, satisfying a condition shown by a formula (1): 0.1≤A600 / A300.SELECTED DRAWING: Figure 10
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing hydrogen, a photocatalyst, and a method for producing the photocatalyst. [Background technology]

[0002] Hydrogen is expected to be used as an alternative energy source to fossil fuels. Known methods for producing hydrogen include extracting hydrogen from gas obtained by burning fossil fuels and extracting hydrogen from water by electrolysis. In order to realize a carbon-neutral society, there is a need to develop hydrogen production technologies that can replace existing methods that involve carbon dioxide emissions and large amounts of electricity consumption. Oxide semiconductors such as titanium dioxide are known as substances (photocatalysts) that decompose water into oxygen and hydrogen when irradiated with light (see, for example, Non-Patent Document 1), and are expected to be used as a means of producing hydrogen. However, there are many challenges to practically using oxide semiconductors as a means of producing hydrogen, one of which is improving the light utilization efficiency of oxide semiconductors. Specifically, while oxide semiconductors exhibit high photocatalytic activity for ultraviolet light, they have low photocatalytic activity for visible light. This makes it difficult to efficiently produce hydrogen using natural light. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Journal of Materials Science 46 (2011) 855-874 Summary of the Invention [Problem to be solved by the invention]

[0004] In order to popularize hydrogen production methods using titanium dioxide, it is important to increase the efficiency of visible light utilization of oxide semiconductors as photocatalysts and thereby increase the efficiency of hydrogen production. In view of the above circumstances, an object of the present disclosure is to provide a hydrogen production method having excellent hydrogen production efficiency using a photocatalyst, a photocatalyst having excellent hydrogen production efficiency, and a method for producing a photocatalyst having excellent hydrogen production efficiency. [Means for solving the problem]

[0005] The present disclosure includes the following aspects. <1> decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The oxide semiconductor has an absorbance A at 300 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy. 300 and absorbance A at 600 nm 600 And the formula (1): 0.1 ≦ A 600 / A 300 A method for producing hydrogen that satisfies the above conditions. <2> decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The method for producing hydrogen, wherein the oxide semiconductor is subjected to a treatment of twisting operation under a pressure of 5 GPa or more. <3> The oxide semiconductor contains brookite-type TiO2. <1> or <2> The method for producing hydrogen according to claim 1. <4> The oxide semiconductor includes columbite-type TiO2. <1> or <2> The method for producing hydrogen according to claim 1. <5> The oxide semiconductor includes rocksalt type ZnO. <1> or <2> The method for producing hydrogen according to claim 1. <6> decomposing water in the presence of the sacrificial agent into hydrogen and oxygen; <1> or <2> The method for producing hydrogen according to claim 1. <7> said sacrificial agent comprises methanol; <6> The method for producing hydrogen according to claim 1. <8> Decomposing water into hydrogen and oxygen in the presence of a promoter; <1> or <2> The method for producing hydrogen according to claim 1. <9> A photocatalyst for splitting water into hydrogen and oxygen, comprising: Absorbance A at 300 nm in the absorption spectrum obtained by UV-Vis spectroscopy 300 and absorbance A at 600 nm 600 And the formula (1): 0.1 ≦ A 600 / A300 A photocatalyst comprising an oxide semiconductor that satisfies the above condition. <10> The oxide semiconductor contains brookite-type TiO2. <9> The photocatalyst described in <11> The oxide semiconductor includes columbite-type TiO2. <9> The photocatalyst described in <12> The oxide semiconductor includes rocksalt type ZnO. <9> The photocatalyst described in <13> 1. A method for producing a photocatalyst for splitting water into hydrogen and oxygen, comprising the steps of: A method for producing a photocatalyst, comprising: subjecting an oxide semiconductor contained in the photocatalyst to a treatment in which the oxide semiconductor is twisted while being subjected to a pressure of 5 GPa or more. <14> After the treatment, the oxide semiconductor has an absorbance A at 300 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy. 300 and absorbance A at 600 nm 600 And the formula (1): 0.1 ≦ A 600 / A 300 Fulfill the conditions of <13> A method for producing the photocatalyst described in claim 1. Effect of the Invention

[0006] According to the present disclosure, there are provided a hydrogen production method with excellent hydrogen production efficiency using a photocatalyst, a photocatalyst with excellent hydrogen production efficiency, and a method for producing this photocatalyst. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a diagram illustrating a schematic configuration of an apparatus for performing HPT treatment on an oxide semiconductor. [Diagram 2] FIG. 1 is a diagram showing the appearance of the photocatalyst obtained in Production Example 1. [Diagram 3] FIG. 2 is a diagram showing the XRD diffraction pattern of the photocatalyst obtained in Production Example 1. [Figure 4] FIG. 2 is a diagram showing the Raman spectrum of the photocatalyst obtained in Production Example 1. [Diagram 5] 1 is an SEM image of the photocatalyst obtained in Production Example 1. [Figure 6]FIG. 2 is a diagram showing the absorption spectrum of the photocatalyst obtained in Production Example 1, obtained by ultraviolet-visible spectroscopy. [Figure 7] FIG. 2 is a diagram showing the XRD diffraction pattern of the photocatalyst obtained in Production Example 2. [Figure 8] FIG. 2 is a diagram showing the Raman spectrum of the photocatalyst obtained in Production Example 2. [Figure 9] 1 is an SEM image of the photocatalyst obtained in Production Example 2. [Figure 10] FIG. 2 is a diagram showing an absorption spectrum obtained by ultraviolet-visible spectroscopy of the photocatalyst obtained in Production Example 2. [Figure 11] FIG. 2 is a diagram showing the XRD diffraction pattern of the photocatalyst obtained in Production Example 3. [Figure 12] FIG. 2 is a diagram showing the EPR spectrum of the photocatalyst obtained in Production Example 3. [Figure 13] FIG. 2 is a diagram showing an absorption spectrum obtained by ultraviolet-visible spectroscopy of the photocatalyst obtained in Production Example 3. [Figure 14] FIG. 1 is a diagram showing the spectrum of a high-pressure mercury lamp used in a H2 generation test. [Figure 15] FIG. 1 shows the results of an H2 production test carried out in Example 2. [Figure 16] FIG. 1 shows the results of an H2 production test carried out in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0009] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0010] <Hydrogen production method 1> The first embodiment of the present disclosure is decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The oxide semiconductor has an absorbance A at 300 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy. 300 and absorbance A at 600 nm 600 And the formula (1): 0.1 ≦ A 600 / A 300 This is a method for producing hydrogen that satisfies the above conditions.

[0011] Oxide semiconductors, which have been known as photocatalysts, show a rapid drop in absorbance when the wavelength of light exceeds 300 nm, and show almost no absorption in the visible range. In contrast, the photocatalyst used in the method of the present disclosure shows some absorption even for light in the visible range. Therefore, light in a wider wavelength range than conventional methods can be used to produce hydrogen.

[0012] As will be shown in the examples described later, when an oxide semiconductor satisfying formula (1) is used as a photocatalyst, the efficiency of hydrogen production is improved compared to when an oxide semiconductor not satisfying formula (1) is used as a photocatalyst. This is believed to be because the photocatalytic activity of the oxide semiconductor in the visible range is improved, thereby increasing the efficiency of use of light irradiated to the photocatalyst.

[0013] From the viewpoint of increasing the efficiency of light utilization by the photocatalyst, the oxide semiconductor contained in the photocatalyst should have a conductivity of 0.15≦A 600 / A 300 It is preferable to satisfy the condition 0.2≦A 600 / A 300 It is more preferable to satisfy the condition 0.3≦A 600 / A 300 It is more preferable to satisfy the following condition.600 / A 300 The upper limit value of is not particularly limited, and may be, for example, 1.0, 0.8, 0.6, or 0.4.

[0014] From the viewpoint of increasing the efficiency of light utilization by the photocatalyst, the oxide semiconductor contained in the photocatalyst satisfies the formula (2): 0.1≦A 500-700(min) / A 300 It is preferable to satisfy the condition 0.15≦A 500-700(min) / A 300 It is more preferable to satisfy the condition 0.2≦A 500-700(min) / A 300 It is more preferable to satisfy the condition 0.3≦A 500-700(min) / A 300 It is more preferable to satisfy the following condition. 500-700(min) / A 300 The upper limit value of is not particularly limited, and may be, for example, 1.0, 0.8, 0.6, or 0.4. In formula (2), A 500-700(min) means the minimum value of absorbance in the range of 500 nm to 700 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy.

[0015] In the method of the present disclosure, the oxide semiconductor contained in the photocatalyst itself exhibits excellent light utilization efficiency, and therefore, for example, the hydrogen production efficiency can be improved without supporting a metal as a promoter on the oxide semiconductor or doping the oxide semiconductor with a different element. In other words, the method disclosed herein can achieve efficient hydrogen production using photocatalysis without increasing production costs due to metal loading or doping, or generating waste liquid due to chemical treatment.

[0016] The oxide semiconductor contained in the photocatalyst is not particularly limited as long as it exhibits the property of decomposing water into hydrogen and oxygen when irradiated with light (photocatalytic activity).Specific examples of oxide semiconductors include TiO2, ZnO, SnO2, In2O3, ITO, NiO, VO2, and SrTiO3. The oxide semiconductor may or may not be doped with a different element. The oxide semiconductor contained in the photocatalyst may be of one type or of two or more types.

[0017] From the viewpoint of improving the efficiency of light utilization by the photocatalyst, it is preferable that the oxide semiconductor contained in the photocatalyst contains at least one type selected from the group consisting of brookite-type TiO2, columbite-type TiO2, and rocksalt-type ZnO. In this disclosure, brookite-type TiO2 means TiO2 having a brookite (orthorhombic) crystal structure, columbite-type TiO2 means TiO2 having a columbite crystal structure, and rock salt-type ZnO means ZnO having a rock salt (rock salt) crystal structure.

[0018] From the viewpoint of increasing the efficiency of light utilization by the photocatalyst, it is preferable that the oxide semiconductor contained in the photocatalyst contains at least one selected from the group consisting of black brookite-type TiO2, high pressure columbite-type TiO2, and high pressure rocksalt-type ZnO. In this disclosure, black brookite-type TiO2 means brookite-type TiO2 that is black, high-pressure columbite-type TiO2 means columbite-type TiO2 that has been subjected to the HPT treatment described later, and high-pressure rock salt-type ZnO means rock salt-type ZnO that has been subjected to the HPT treatment described later.

[0019] An oxide semiconductor satisfying formula (1) can be obtained, for example, by subjecting a raw material oxide semiconductor to a twisting treatment while applying a pressure of 5 GPa or more. Hereinafter, the process of performing the twisting operation under a pressure of 5 GPa or more is also referred to as HPT (High-Purity Tortion) process.

[0020] As shown in the examples described later, an oxide semiconductor that has been subjected to HPT treatment has a higher absorbance in the visible region than an oxide semiconductor before the HPT treatment. In other words, an oxide semiconductor that satisfies formula (1) can be obtained by subjecting an oxide semiconductor to HPT treatment. Although the reason why the absorbance of oxide semiconductors in the visible range increases by HPT treatment is not entirely clear, it is thought that, for example, the interstitial oxygen defects that occur in the crystal structure of oxide semiconductors plastically deformed by HPT treatment have some effect, or that the integration of oxide semiconductor particles by HPT treatment has some effect.

[0021] There is no particular limitation on the method for carrying out the HPT treatment of the oxide semiconductor. For example, the HPT treatment may be carried out according to the following procedure using an HPT apparatus having the configuration shown in FIG. The HPT apparatus shown in Fig. 1 is equipped with a pair of anvils (Upper Anvil / Lower Anvil) for applying pressure to a sample. At least one of the anvils (Lower Anvil in Fig. 1) is rotatable in a direction perpendicular to the direction of pressure applied to the sample.

[0022] When performing HPT treatment using the HPT apparatus shown in Figure 1, first, a sample of oxide semiconductor powder is placed between a pair of anvils. Next, the anvils are closed to apply pressure to the powder (pressure application operation). Next, while pressure is being applied to the sample, one of the anvils is rotated in a direction perpendicular to the direction of pressure applied to the sample (twisting operation). The state of the obtained oxide semiconductor can be controlled by changing the conditions of the HPT treatment (pressure, the number of rotations of the device in the twisting operation, temperature, and the like).

[0023] The pressure applied to the sample in the HPT treatment is not particularly limited as long as it is 5 GPa or more, and can be selected depending on the type of sample and the desired physical properties as a photocatalyst. From the viewpoint of increasing the absorbance of the oxide semiconductor in the visible region, the pressure applied to the sample is preferably 5 GPa or more, more preferably 6 GPa or more, and may be 10 GPa or less, 9 GPa or less, or 8 GPa or less.

[0024] The conditions for the twisting operation applied to the sample are not particularly limited, and can be selected depending on the type of sample and the desired physical properties as a photocatalyst. From the viewpoint of increasing the absorbance of the oxide semiconductor in the visible region, the number of rotations of the device in the twisting operation is preferably 0.5 rotations or more, more preferably 1 rotation or more, and even more preferably 2 rotations or more. The number of rotations of the device in the twisting operation may be 20 rotations or less.

[0025] The temperature of the sample during the HPT treatment is not particularly limited and can be selected depending on the type of sample and the desired physical properties as a photocatalyst, for example, it may be selected from the range of 273 K (0° C.) to 523 K (250° C.).

[0026] Whether or not an oxide semiconductor has been subjected to HPT treatment can be confirmed by various methods as shown in the examples described later, for example, by comparing the physical properties such as color, particle structure, and crystal structure of a raw oxide semiconductor and an oxide semiconductor after HPT treatment.

[0027] In the method of the present disclosure, the method for decomposing water into hydrogen and oxygen using a photocatalyst is not particularly limited, and may be carried out by a known method.

[0028] Optionally, the disclosed methods may employ a sacrificial agent that acts to prevent the recombination of electron-hole pairs generated by excitation of the photocatalyst (specifically, by injecting the electrons donated by the sacrificial agent into the holes), thereby facilitating hydrogen production. Specific examples of sacrificial agents include monohydric alcohols such as methanol and ethanol; dihydric alcohols such as ethylene glycol and propylene glycol; trihydric alcohols such as glycerin; carboxylic acids such as formic acid, acetic acid, and oxalic acid; amines such as ethylenediaminetetraacetic acid (EDTA) and triethanolamine (TEA), and sugars. The sacrificial agents may be used alone or in combination of two or more.

[0029] If necessary, a co-catalyst may be used in the method of the present disclosure. Specific examples of the co-catalyst include platinum, gold, palladium, ruthenium, rhodium, silver, copper, and iridium. The co-catalyst may be supported on the surface of the oxide semiconductor used as a photocatalyst, or may not be supported on the surface. The promoter may be used alone or in combination of two or more kinds.

[0030] <Hydrogen production method 2> The second embodiment of the present disclosure is decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The oxide semiconductor is in a state where it has been subjected to a twisting operation under a pressure of 5 GPa or more.

[0031] In the above method, a photocatalyst containing an oxide semiconductor that has been subjected to HPT treatment is used. As shown in the examples described below, an oxide semiconductor that has been subjected to HPT treatment has a higher absorbance in the visible range than an oxide semiconductor that has not been subjected to HPT treatment. Therefore, by using an oxide semiconductor that has been subjected to HPT treatment as a photocatalyst, the light utilization efficiency is improved, and hydrogen can be produced efficiently.

[0032] The details and preferred aspects of the photocatalyst or oxide semiconductor in the second embodiment are similar to the details and preferred aspects of the photocatalyst or oxide semiconductor in the first embodiment.

[0033] <Photocatalyst> A third embodiment of the present disclosure is a photocatalyst for splitting water into hydrogen and oxygen, Absorbance A at 300 nm in the absorption spectrum obtained by UV-Vis spectroscopy 300 and absorbance A at 600 nm 600 And the formula (1): 0.1 ≦ A 600 / A 300 The photocatalyst includes an oxide semiconductor that satisfies the above condition.

[0034] The details and preferred aspects of the photocatalyst or oxide semiconductor in the second embodiment are similar to the details and preferred aspects of the photocatalyst or oxide semiconductor in the first embodiment.

[0035] <Photocatalyst manufacturing method> A fourth embodiment of the present disclosure is a method for producing a photocatalyst for splitting water into hydrogen and oxygen, comprising the steps of: The method for producing the photocatalyst includes subjecting the oxide semiconductor contained in the photocatalyst to a treatment in which the oxide semiconductor is twisted while being subjected to a pressure of 5 GPa or more.

[0036] The details and preferred aspects of the photocatalyst or oxide semiconductor in the fourth embodiment are similar to the details and preferred aspects of the photocatalyst or oxide semiconductor in the first embodiment.

[0037] The details and preferred aspects of the HPT treatment in the fourth embodiment are similar to the details and preferred aspects of the HPT treatment in the first embodiment. EXAMPLES

[0038] Hereinafter, the embodiments of the present disclosure will be described in more detail based on examples, but the present disclosure is not limited to these examples.

[0039] <Photocatalyst Manufacturing Example 1: Brookite-type TiO2> Brookite-type TiO2 powder was used as the raw material for the photocatalyst. 277 mg of this powder was pressed under a pressure of 380 MPa to obtain a pellet. Next, the pellet was subjected to HPT treatment using an apparatus with the structure shown in Figure 1. The pressure condition for the HPT treatment was 6 GPa, the twisting operation was performed at a rotation speed of 1 rpm for one rotation, and the temperature conditions were 300 K (27°C), 373 K (100°C), and 473 K (200°C), respectively. Figure 2 shows the appearance of the sample before HPT treatment (Powder), the sample after HPT treatment at 300K (T=300K), the sample after HPT treatment at 373K (T=373K), and the sample after HPT treatment at 473K (T=473K). As shown in Figure 2, the color of the sample changed from white before HPT treatment to light gray, dark gray, and black as the treatment temperature increased. The change in the color of the sample is thought to indicate that oxygen vacancies were formed in the sample by the HPT treatment.

[0040] (X-ray diffraction and Raman spectroscopy) X-ray diffraction (XRD) and Raman spectroscopy were performed on the samples before and after the HPT treatment. The diffraction pattern obtained by XRD under the conditions of CuKα radiation and wavelength λ = 0.1542 nm is shown in Figure 3. The Raman spectrum obtained under the condition of wavelength λ = 532 nm is shown in Figure 4. It was confirmed that the brookite phase (orthorhombic) was expressed in the sample, as shown in Figure 3. As shown in Figure 4, the peak shift in Raman spectroscopy confirmed that the average bond distance between Ti and oxygen had become longer, and oxygen lattice defects had occurred.

[0041] (Observation of particle shape) The particle shape of each sample was observed using a 15 keV scanning electron microscope (SEM), and the results are shown in Figure 5. As shown in Figure 5, compared to the powder before HPT treatment (upper left: (a)), the sample after HPT treatment at 300 K (upper right: (b)), the sample after HPT treatment at 373 K (lower left: (c)), and the sample after HPT treatment at 473 K (lower right: (d)) were found to have particles formed by the integration of particles before the treatment.

[0042] (UV-Vis measurement) The absorption spectrum of each sample was obtained by UV-Vis spectroscopy, and the results are shown in Figure 6. As shown in FIG. 6, the absorbance in the visible range of the sample after HPT treatment was increased compared to the sample before HPT treatment. The sample after HPT treatment (T = 473 K) had an absorbance of A at 300 nm. 300 and absorbance A at 600 nm600 A calculated from 600 / A 300 The value of A is 0.38, and the formula (1): 0.1≦A 600 / A 300 The conditions were met. The sample after HPT treatment (T = 373 K) had an absorbance of A at 300 nm. 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.30 and the formula (1): 0.1≦A 600 / A 300 The conditions were met. The sample after HPT treatment (T = 300K) has an absorbance of A at 300 nm. 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.18, and the formula (1): 0.1≦A 600 / A 300 The conditions were met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.03 and the formula (1): 0.1≦A 600 / A 300 did not meet the conditions.

[0043] The sample after HPT treatment (T = 473 K) had an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) The value of A is 0.37 and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were met. The sample after HPT treatment (T = 373 K) had an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) The value of A is 0.27 and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were met. The sample after HPT treatment (T = 300K) has an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) The value of A is 0.18, and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) The value of A is 0.02 and the formula (2): 0.1≦A 500-700(min) / A 300 did not meet the conditions.

[0044] <Photocatalyst Manufacturing Example 2: Columbite-type TiO2> The photocatalyst raw material used was TiO2 powder with an anatase crystal structure. 260 mg of this powder was subjected to HPT treatment using the device shown in Figure 1. The pressure condition for the HPT treatment was 6 GPa, the twisting operation was performed for 15 revolutions at a rotation speed of 1 rpm, and the temperature condition was 300 K (27 °C).

[0045] (X-ray diffraction and Raman spectroscopy) X-ray diffraction (XRD) and Raman spectroscopy were performed on the sample before HPT treatment (Powder) and the sample after HPT treatment (HPT). Figure 7 shows the diffraction pattern obtained by XRD under conditions of CuKα radiation and wavelength λ = 0.1542 nm. Figure 8 shows the Raman spectrum obtained under conditions of wavelength λ = 532 nm. As shown in Figs. 7 and 8, peaks derived from the columbite-type crystal structure were prominent in the sample after the HPT treatment.

[0046] (Observation of particle shape) The particle shape of each sample was observed using a 15 keV scanning electron microscope (SEM), and the results are shown in Figure 9. As shown in Figure 9, compared to the powder before HPT treatment (left: (a)), the sample after HPT treatment (right: (b)) was found to have particles formed by the particles before treatment integrating together.

[0047] (UV-Vis measurement) The absorption spectrum of each sample was obtained by UV-Vis spectroscopy, and the results are shown in Figure 10. As shown in FIG. 10, the sample after HPT treatment had increased absorbance in the visible range compared to the sample before HPT treatment. The absorbance A at 300 nm of the sample after HPT treatment (HPT) 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.46, and the formula (1): 0.1≦A 600 / A 300 The conditions were met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0 and the formula (1): 0.1 ≦ A 600 / A 300 did not meet the conditions.

[0048] The absorbance A at 300 nm of the sample after HPT treatment (HPT) 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) / A 300 The value of A is 0.40 and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) / A 300 The value of is 0 and formula (2): 0.1 ≦ A 500-700(min) / A 300 did not meet the conditions.

[0049] <Photocatalyst manufacturing example 3: Rock salt type ZnO> ZnO powder was used as the raw material for the photocatalyst. 400 mg of this powder was subjected to HPT treatment using the device shown in Figure 1. The pressure condition for the HPT treatment was 6 GPa, and the rotation speed for the twisting operation was 1 rpm, with the rotation numbers N being 1 / 16, 1 / 4, 1, and 4. The temperature condition was 300 K (27°C).

[0050] (X-ray diffraction and Raman spectroscopy) X-ray diffraction (XRD) and Raman spectroscopy were performed on the sample before HPT treatment (Powder) and each sample after HPT treatment (N=1 / 16, N=1 / 4, N=1, and N=4). The diffraction pattern obtained by XRD under the conditions of CuKα radiation and wavelength λ=0.1542 nm is shown in Figure 11. As shown in FIG. 11, a rock salt ZnO type crystal structure was suggested in the sample.

[0051] (EPR measurement) EPR (Electron Paramagnetic Resonance) was performed on each sample, and the obtained EPR spectrum is shown in FIG. The results shown in FIG. 12 suggest that radical oxygen lattice defects were generated based on the appearance of a peak in the EPR spectrum.

[0052] (UV-Vis measurement) The absorption spectrum of each sample was obtained by UV-Vis spectroscopy, and the results are shown in Figure 13. As shown in FIG. 13, the sample after the HPT treatment had increased absorbance in the visible range compared to the sample before the HPT treatment. After HPT treatment, the absorbance at 300 nm (A = 4) was 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.20 and the formula (1): 0.1≦A 600 / A 300 The conditions were met. After HPT treatment, the samples (N=1 / 16, N=1 / 4, or N=1) were measured for absorbance at 300 nm, A 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The values ​​of A and B are all 0.10, and the formula (1): 0.1≦A 600 / A 300 The conditions were met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and absorbance A at 600 nm 600 A calculated from 600 / A 300 The value of A is 0.01 and the formula (1): 0.1≦A 600 / A 300 did not meet the conditions.

[0053] After HPT treatment, the absorbance at 300 nm (A = 4) was 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) The value of A is 0.18, and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were met. After HPT treatment, the samples (N=1 / 16, N=1 / 4, or N=1) were measured for absorbance at 300 nm, A 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) / A 300 The values ​​of A and B are all 0.09, and the formula (2): 0.1≦A 500-700(min) / A 300 The conditions were slightly not met. The sample (Powder) before HPT treatment had an absorbance of A at 300 nm. 300 and the minimum absorbance value in the range of 500 nm to 700 nm. 500-700(min) / A 300 The value of is 0 and formula (2): 0.1 ≦ A 500-700(min) / A 300 did not meet the conditions.

[0054] <Example 1> Using the sample obtained in Production Example 1, a test for generating hydrogen by decomposition of water was carried out. A continuous quartz reactor was used as the apparatus, and 100 mg of the sample was dispersed in 500 ml of water containing 1 M NaHCO3 as the reaction medium. Ar gas was bubbled through a hole at the top of the reactor at a flow rate of 3 mL / min and passed through the reaction medium. The photocatalytic reaction was carried out at 0.5 W / cm using a high-pressure mercury lamp (Cenlite, HL400BH-8, 400 W) installed in the reactor. 2 The experiment was carried out at an intensity of 10 ...

[0055] When the sample HPT-treated at T = 473 K was used as a photocatalyst, the hydrogen production rate after 2 hours from the start of the test was 10.5 μmol / h m 2 In contrast, when the sample before HPT treatment was used, the hydrogen production rate after 2 hours from the start of the test was 2 μmol / h m 2 It was.

[0056] (Reference example: CO generation test) Using the sample obtained in Production Example 1, a test was carried out to generate CO by reduction of CO2. As a result, when the sample that had been HPT-treated at T = 473 K was used as a photocatalyst, the CO production rate after 2 hours from the start of the test was 13 μmol / h m 2 In contrast, when the sample before HPT treatment was used, the CO production rate after 2 hours from the start of the test was 3 μmol / h m 2 From the above results, it was found that the sample obtained in Production Example 1 has the ability to reduce CO2 and generate CO.

[0057] <Example 2> Using the sample obtained in Production Example 2, a test for producing hydrogen by decomposition of water was carried out. The tests were carried out under the full light arc of a 300 W UV xenon light source using a mixture of 50 mg of sample, 27 mL of water, 3 mL of methanol (sacrificial agent), and 0.25 mL of HPtCl 6·6H O (0.01 M). The results are shown in Figure 15.

[0058] As shown in FIG. 15, the sample after the HPT treatment (HPT) showed a larger amount of hydrogen production than the sample before the HPT treatment (Powder).

[0059] <Example 3> Using the sample obtained in Production Example 3, a test for producing hydrogen by decomposition of water was carried out. The test was carried out on a 193 cm 3 The experiment was carried out under xenon light irradiation (300 W) using a cylindrical batch reactor. A circulation pump was connected to the reactor to easily move the gas flow in the circuit. Since oxygen may be generated in the water decomposition reaction, it was necessary to ensure that there was no oxygen in the system. To this end, the gas in the system was evacuated using a vacuum pump and argon gas. This was repeated several times until all the oxygen gas was removed. 50 mg of the sample was dispersed in a mixture of 27 mL of water, 3 mL of methanol (sacrificial agent), and Pt(NH3)4(NO3)2 (0.01 M) for depositing Pt as a cocatalyst. Sampling from the reactor was carried out after a given time using a gas sampling valve consisting of two four-way valves. Finally, the amount of hydrogen produced was measured using a gas chromatograph equipped with a molecular sieve column and a thermal conductivity detector (TCD-GC). The results are shown in Figure 16.

[0060] As shown in FIG. 16, the samples after the HPT treatment (N=4) showed a larger amount of hydrogen production than the sample before the HPT treatment (Powder).

Claims

1. decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The oxide semiconductor has an absorbance A at 300 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy. 300 and absorbance A at 600 nm 600 and formula (1): 0.1≦A 600 / A 300 A method for producing hydrogen that satisfies the above conditions.

2. decomposing water into hydrogen and oxygen using a photocatalyst including an oxide semiconductor; The method for producing hydrogen, wherein the oxide semiconductor has been subjected to a treatment of twisting while applying a pressure of 5 GPa or more.

3. The oxide semiconductor is a brookite-type TiO 2 The method for producing hydrogen according to claim 1 or 2, comprising:

4. The oxide semiconductor is a columbite-type TiO 2 The method for producing hydrogen according to claim 1 or 2, comprising:

5. The method for producing hydrogen according to claim 1 , wherein the oxide semiconductor includes rocksalt type ZnO.

6. 3. The method for producing hydrogen according to claim 1 or claim 2, wherein water is decomposed into hydrogen and oxygen in the presence of a sacrificial agent.

7. 7. The method for producing hydrogen as claimed in claim 6, wherein said sacrificial agent comprises methanol.

8. 3. The method for producing hydrogen according to claim 1 or 2, wherein water is decomposed into hydrogen and oxygen in the presence of a promoter.

9. A photocatalyst for splitting water into hydrogen and oxygen, comprising: Absorbance A at 300 nm in the absorption spectrum obtained by ultraviolet-visible spectroscopy 300 and absorbance A at 600 nm 600 and formula (1): 0.1≦A 600 / A 300 A photocatalyst comprising an oxide semiconductor that satisfies the above condition.

10. The oxide semiconductor is a brookite-type TiO 2 The photocatalyst according to claim 9 .

11. The oxide semiconductor is a columbite-type TiO 2 The photocatalyst according to claim 9 .

12. The photocatalyst according to claim 9 , wherein the oxide semiconductor comprises rocksalt type ZnO.

13. 1. A method for producing a photocatalyst for splitting water into hydrogen and oxygen, comprising the steps of: A method for producing a photocatalyst, comprising: subjecting an oxide semiconductor contained in the photocatalyst to a treatment in which the oxide semiconductor is twisted while being subjected to a pressure of 5 GPa or more.

14. After the treatment, the oxide semiconductor has an absorbance A at 300 nm in an absorption spectrum obtained by ultraviolet-visible spectroscopy. 300 and absorbance A at 600 nm 600 and formula (1): 0.1≦A 600 / A 300 The method for producing a photocatalyst according to claim 13, which satisfies the above condition.